Integrating Complementary Medicine Into the Care of Childhood Cancer Survivors: A Brief Report on the Preliminary Framework and Implementation of an Educational Program - Lam, Chun Sing; Au, Kwok Yin; Hung, Hing Yu; Chou, Ho Wing; Leung, Alex Wing Kwan; Li, Chi Kong; Koon, Ho Kee; Cheung, Yin Ting (Frontiers in Rehabilitation Sciences, 2022)
Background Existing educational programs typically include limited information on traditional, complementary, and integrative medicine (TCIM) for survivors of childhood cancer. Objectives This brief report presents the preliminary results of an educational program that aims to promote the safe and effective use of Chinese medicine (CM) among survivors in Hong Kong. Methods Survivors of childhood cancer, their caregivers, and oncology practitioners were invited to participate in a program that consists of two didactic seminars and a written educational booklet that disseminated information on the use of CM. A structured questionnaire was used to evaluate participants' receptivity toward and perceived relevance of the program. The Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework was used to discuss the impact of the intervention. Results Reach: A total of 174 participants attended the seminars, and the seminar recording received over 380 views on social media platforms since April 2021. The hardcopy of the educational booklet was distributed to 43 recipients. The web-version of the booklet was sent to 67 participants and downloaded 143 times. Efficacy: The majority found that the content of the seminar useful (mean score = 5.04/6 points), especially the CM exercise (mean score = 4.88/6 points) and dietary advice (mean score = 4.99/6 points). Intention to adopt: The survivors (or their caregivers) reported that they would adopt advice on food therapies (83.3%) and traditional Chinese health exercises (55.6%) during survivorship. Conclusion The preliminary data on patient preferences will be applied to further develop educational materials and to establish a TCIM referral network within the cancer survivor community.